FAKTOR-FAKTOR PENENTU KINERJA SAHAM PERUSAHAAN SETELAH PENAWARAN UMUM PERDANA - DITA, KHARISMA (Jurnal Ilmu Manajemen (JIM), 2013)
This study was conducted with the objective of identifying and analyze factors that affect the stock performance one year after carrying out Initial Public Offering. Stock performance is measured using the method of buy and hold abnormal return (BHAR). Based research gap, the independent variables studied were price earnings ratio, underwriter reputation, firm size, firm age, book to market ratio and percentage of shares offered. Samples taken in this study consisted of 95 companies that carry out initial public offerings in the 2007-2011 in Indonesia Stock Exchange. Data is analyzed using multiple regression analysis techniques. The results of this study showed variables price earnings ratio and percentage of shares offered have negative effect on stock performance. Variables underwriter reputation, firm size, firm age and book to market ratio does not affect the stock performance one year after implementing the IPO. Keywords: IPO, BHAR, Financial Variables.